EPEN-18. CROSS-SPECIES GENOMICS IDENTIFIES GLI2 AS AN ONCOGENE OF C11orf95 FUSION-POSITIVE SUPRATENTORIAL EPENDYMOMA. (4th December 2020) - Zheng, Tuyu; Ghasemi, David R; Okonechnikov, Konstantin; Korshunov, Andrey; Sill, Martin; Hübner, Jens-Martin; Maaß, Kendra K; Snuderl, Matija; Gojo, Johannes; Schüller, Ulrich; Gerber, Nicolas U; Hernáiz-Driever, Pablo; et al.
Abstract: The majority of supratentorial ependymomas (ST-EPN) are driven by fusions between RELA and a zinc finger containing gene, C11orf95 . Apart from fusions to the Hippo effector YAP1, which affects a small group of infant patients, the oncogenic mechanism of remaining ST-EPNs is unclear. Aiming at refining the molecular classification of ST-EPNs, we analyzed methylation profiles, RNA and DNA sequencing results as well as clinical data in a cohort of 617 ST-EPNs. Unsupervised clustering analysis of DNA methylation data revealed four distinct clusters that formed in addition to the known molecular groups ST-EPN-RELA and –YAP1. Tumors within these additional clusters were characterized by fusions of C11orf95 to numerous fusion partners different from RELA, e.g. MAML2, MAML3, NCOA2 and SS18, suggesting a general role of C11orf9 5 in tumorigenesis of ST-EPN. Transforming capacity of newly identified fusion genes was validated using an electroporation-based in vivo gene transfer technology. All fusion genes were sufficient to drive malignant transformation in the cerebral cortex of mice and resulting tumors faithfully recapitulated molecular characteristics of their human counterparts. We found that both, the partner gene and the zinc finger DNA binding domain of C11orf95, were essential to exert tumorigenesis. When exploring genes commonly upregulated in C11orf95 fusion-expressing tumors of human and murine origin, the Sonic Hedgehog effector gene Gli2 was identified as a promising downstream target. Subsequent co-expression of C11orf95:RELA and a dominant negative form of Gli2 indeed hampered tumorigenesis. We thus propose GLI2 as a potential therapeutic downstream target of C11orf95 fusion-dependent oncogenic signaling in ST-EPN.